2018
DOI: 10.4153/s0008414x18000081
|View full text |Cite
|
Sign up to set email alerts
|

The Primitive Spectrum and Category  for the Periplectic Lie Superalgebra

Abstract: We solve two problems in representation theory for the periplectic Lie superalgebra pe(n), namely the description of the primitive spectrum in terms of functorial realisations of the braid group and the decomposition of category O into indecomposable blocks.To solve the first problem we establish a new type of equivalence between category O for all (not just simple or basic) classical Lie superalgebras and a category of Harish-Chandra bimodules. The latter bimodules have a left action of the Lie superalgebra b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 26 publications
1
52
0
Order By: Relevance
“…For a simple reflection sW, we have the right exact twisting functor Ts on O(g,frakturbtrue0¯) as in [11, §4.3], see also [1, 2]. Since these functors satisfy the braid relations, see, for example, [20, 30], we have the twisting functor Tw0 defined via composition with respect to an arbitrary reduced expression for w0.…”
Section: Parabolic Category Scriptomentioning
confidence: 99%
See 2 more Smart Citations
“…For a simple reflection sW, we have the right exact twisting functor Ts on O(g,frakturbtrue0¯) as in [11, §4.3], see also [1, 2]. Since these functors satisfy the braid relations, see, for example, [20, 30], we have the twisting functor Tw0 defined via composition with respect to an arbitrary reduced expression for w0.…”
Section: Parabolic Category Scriptomentioning
confidence: 99%
“…Moreover, its inverse (as described in the proof of [21, Theorem 8.1]) is by [1, Theorem 4.1], a cohomology functor of a completion functor. In [11, Section 4.2], it is shown that completion functors can be defined on O(g,frakturptrue0¯) as well and satisfy the analogue of (). We denote the corresponding cohomology functor (both for frakturg and g0¯) by boldG.…”
Section: Parabolic Category Scriptomentioning
confidence: 99%
See 1 more Smart Citation
“…For simple Lie superalgebras, the analogue of Duflo's theorem is established by Musson in [Mu1] using the results of finite ring extensions in [Le1]. Following methods in [Le1,Mu1], it is shown in [CC,Section 4.1] that Duflo's theorem remains valid for arbitrary quasireductive Lie superalgebras. Therefore, it is natural to make an identification between annihilator ideals of simple Whittaker modules and primitive ideals from the category O.…”
mentioning
confidence: 99%
“…These assumptions and choice will be referred to as (A1), (A2) and (A3) in this article; see also examples in (2.3.2). Lie superalgebras g satisfying these assumptions are referred to as Lie superalgebras of type I-0 (see [CC]) and fit into the framework of [CC,Section 4]. In particular, for such Lie superalgebras there is a number of basic properties of the twisting functors developed in [CC,Section 4.3] that are to be used in the present paper.…”
mentioning
confidence: 99%